Implementasi Sistem Menu Engineering untuk Peningkatan Kualitas Menu di X Coffee Eatery Tebet - Rinaldi, Alvin; Hiskandar, Hiskandar (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
Cafes or coffee shops have grown rapidly and become an important part of the urban lifestyle. In the face of growing market demand, improving menu quality is a key focus for every cafe. Menu engineering systems provide a solid structural foundation for understanding and managing each stage in creating a dish. The purpose of this research is to find out how the level of popularity of the menu at X Coffee Eatery, to find out how the profit level at X Coffee Eatery, and to find out how the menu performance category at X Coffee Eatery. This research uses a descriptive approach with quantitative methods. The results showed that of the 69 menu items, the results can be seen, namely in the X Special menu type 1 menu item which has a popularity level (MM%) of 100%. 16 menu items categorized as star, 4 menus categorized as plowhorse, 23 menus categorized as puzzle and 4 menus categorized as dog. Evaluation is needed for menus with low popularity levels in order to increase popularity through menu engineering methods.